THE EFFECTS OF SUPERNATURAL BEINGS TOWARDS THE MAIN CHARACTER IN CORALINE (2009) BY HENRY SELICK - Mokodompit, Muhammad Andra Anugerah; Balango, Mery; Podungge, Rusni (Pascasarjana, Universitas Negeri Gorontalo, 2024)
The aims of this study is to analyze how the effects of supernatural beings depicted in the main character of Coraline movie by using Dunwich (2002) theory about the effects of supernatural beings towards humans. This research applied Saussure’s Structuralism theory about the relation of Signifier and Signified and using the five interpreting concepts, which consist of Arbitrary and Conventional of sign, Langue and Parole, Binary Opposition and the relation of Syntagmatic and Paradigmatic (1966). In the concept of Arbitrary and Conventional, this study showed that the main character experienced the effects of the influence of supernatural beings towards herself, which resulted in Coraline having supernatural power to communicate with supernatural beings. Further, by using the concept of Langue and Parole, showed the effects of supernatural beings towards herself also affect Coraline's personality. In the concept of Binary Oppositions, there are differences between Coraline’s personality towards her real parents and the other mother, which showed Coraline unhappy and always feel annoyed when she with her real parents, whereas Coraline always happy when she with the other mother. All of these effects leads Coraline to the Obsession Phenomenon that made her having a bad intention to to her real parents, which is to leave her real parents forever. Coraline Syntagmatically get the these effects because of the direct influence of the other mother, whereas Paradigmatically Coraline get these effects because of the dark history of Coraline’s apartement.